Developing undergraduates' awareness of metacognitive knowledge in writing through problem - based learning - Aliyu, Muhammad Mukhtar; Yong, Mei Fung; Abdullah, Mardziah H.; Tan , Bee Hoon (Australian International Academic Centre, 2016)
Metacognitive awareness can improve students’ writing proficiency. Engaging and supporting students in the writing process can increase their metacognitive awareness. This study investigates the effects of a problem-based learning approach on the awareness of metacognitive knowledge of Nigerian undergraduates in writing. An intact class of second-year students in an English composition course participated in the study. The study was conducted over a period of 12 weeks. Quantitative and qualitative methods were used in data collection. A metacognitive questionnaire was administered before and after the PBL treatment. Semi-structured interview was also carried out at the end of the treatment. The results showed significant effects of the PBL approach on the participants’ awareness of metacognitive knowledge of task requirements, personal learning process, strategy use, text and accuracy, problem solving and discourse features. The findings from the interview revealed that the nature of the ill-structured problem, which is related to their real life, and the interactions during the PBL process increased the participants’ awareness of metacognitive knowledge. The findings further showed that PBL approach could be adopted by ESL instructors and teachers to increase students’ awareness of metacognitive knowledge which in turn can enhance their writing proficiency.